2022
DOI: 10.1080/14756366.2022.2038592
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition studies of bacterial α-carbonic anhydrases with phenols

Abstract: The α-class carbonic anhydrases (CAs, EC 4.2.1.1) from the bacterial pathogens Neisseria gonorrhoeae (NgCAα) and Vibrio cholerae (VchCAα) were investigated for their inhibition by a panel of phenols and phenolic acids. Mono-, di- and tri-substituted phenols incorporating additional hydroxyl/hydroxymethyl, amino, acetamido, carboxyl, halogeno and carboxyethenyl moieties were included in the study. The best NgCAα inhibitrs were phenol, 3-aminophenol, 4-hydroxy-benzyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…What is more relevant according to us, is the fact that our study and the preceding ones 2 , although performed on an enzyme thought to belong to S. aureus but which is actually M. sciuri , may bring to attention druggable targets which may lead to antibiotics with a novel mechanism of action. In fact, several groups showed that inhibition of bacterial CAs represents an effective and innovative way for fighting drug resistant bacteria 4 , 5 , with all the scepticism from groups as the one mentioned above that these enzymes could be considered antiinfective drug targets. As far as we know, resistance to sulphonamide CAIs has not been registered for any of the investigated bacterial species, although this phenomenon is erroneously mentioned in ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more relevant according to us, is the fact that our study and the preceding ones 2 , although performed on an enzyme thought to belong to S. aureus but which is actually M. sciuri , may bring to attention druggable targets which may lead to antibiotics with a novel mechanism of action. In fact, several groups showed that inhibition of bacterial CAs represents an effective and innovative way for fighting drug resistant bacteria 4 , 5 , with all the scepticism from groups as the one mentioned above that these enzymes could be considered antiinfective drug targets. As far as we know, resistance to sulphonamide CAIs has not been registered for any of the investigated bacterial species, although this phenomenon is erroneously mentioned in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonic anhydrases (CAs, EC 4.2.1.1), the enzymes which catalyse the interconversion between CO 2 and bicarbonate according to Equations (1) and (2) , are widespread in all life kingdoms, including Bacteria 1–5 . Of the eight genetically distinct CA families known to date, at least four (α-, β-, γ- and ι-CAs) are present in these organisms, in which they play crucial roles related to metabolism, pH regulation, acclimation in different niches in which bacteria grow, but also pathogenesis and virulence in the case of pathogenic species 4–6 . …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups showed that the inhibitors of bacterial CAs may lead to effective compounds for fighting drug resistant bacteria 24–26 , although there was some relevant scepticism that these enzymes could be considered as antiinfective drug targets 27 . It took more than 10 years since the first proposal that bacterial CAs may be new drug targets for the development of antibiotics 28 till the actual in vivo validation of some of them, many of which present in relevant and drug resistant bacterial pathogens, such as Enterococci , Neisseria spp., Helicobacter pylori , etc 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this quite simple reaction slowly occurs in physiological conditions, requiring the aid of an enzyme that strongly accelerates it. Carbonic anhydrases (CAs, EC 4.2.1.1) are ubiquitous metalloenzymes involved in the catalysis of this reaction, and currently eight diverse genetic CA families ( α -, β -, γ -, δ -, ζ -, η -, θ -, and i -CAs) have been reported [ 4 , 5 , 6 , 7 , 8 ]. The fifteen human carbonic anhydrase isoforms (hCAs) belong to the α -family and cover a pivotal role in a multitude of physiological functions such as respiration, transport of carbon dioxide between metabolizing tissues and lungs, pH homeostasis, electrolyte secretion in various tissues/organs, as well as biosynthetic reactions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%